Principles of program design : problem solving with Javascript - Addison, Paul. (Boston, MA : Cengage Learning, 2011)
PRINCIPLES OF PROGRAM DESIGN: PROBLEM SOLVING WITH JAVASCRIPT, International Edition gives your students the fundamental concepts of good program design, illustrated and reinforced by hands-on examples using JavaScript. Why JavaScript? It simply illustrates the programming concepts explained in the book, requires no special editor or compiler, and runs in any browser. Little or no experience is needed because the emphasis is on learning by doing. There are examples of coding exercises throughout every chapter, varying in length and representing simple to complex problems. Students are encouraged to think in terms of the logical steps needed to solve a problem and can take these skills with them to any programming language in the future. To help reinforce concepts for your students, each chapter has a chapter summary, review questions, hand-on activities, and a running case study that students build on in each chapter.
1. The Craft of Programming -- 2. The JavaScript Language -- 3. Objects, Events, and Graphical User Interfaces -- 4. The Sequence Structure -- 5. The Selection Structure -- 6. The Repetition Structure -- 7. Complex Conditions -- 8. Modules and Functions -- 9. Menus and Data Validation -- 10. Arrays -- 11. Building Programs -- 12. Sorting Data -- 13. Recursion.
Includes index.
1
Keywords: Computer programming